Reliable Reliable Path Finding Technique for Mobile Robot - Samal, Chandra Kanta (INFOCOMP Journal of Computer Science, 2020)
This paper we have discussed path planning techniques of mobile robot (Automated Vehicle). Though different researchers had proposed different path planning strategies, each plan has its own advantages and disadvantages. The goal of the research work is to develop an algorithm to find out an optimal path from source to destination along with the obstacles. The path planning algorithm not only minimizes the risk of collision but also reduces the planning time. This method creates a reliable path between desired locations avoiding obstacles. The proposed algorithm is to be implemented to get the reliable path and to be compared with that of the existing algorithm to find the optimized path. The new approach is able to minimize the risk of collision and travelling time with the help of different parameters and simulation software. It has been proved through experimental results that the performance of the proposed algorithm is improved considerably and work efficiently when the shape and size of the image changes. It also turns closely at the corners of the obstacles and also reduces the number of steps without any effect to the steps and corners. Time and space complexity analysis for this algorithm is experimentally tested and implemented.